PRINSIP MELATIH KECERDASAN EMOSI ANAK - Asmaya, Enung (Fakultas Dakwah IAIN Purwokerto, 2010)
Children are God's surrogate. He was born to parents nurtured and raised with love and sincerity. But to realizethe noble task requires both knowledge and skills so as to direct the emotions of vulnerable children so as not to lead toviolence. There are several principles in the child's emotional intelligence training includes: First, the principle of precedence,Second, the principle of good parenting, Third, interactional patterns of communication. Fourth, apply supportive communicationpatterns, Fifth, accept the reality realistically